Fast-Response Hydrogen Sensor Based on γ-Al2O3-Modified Graphene - Bin Shen; Qinglan Zhang; Xinlei Liu; Jiazhe Li; Yu Guan; Dan Xiao (Chemosensors)
The fast response of H2 sensors plays an important role in the early warning of H2 leakage; in this work, a nanoscale <semantics>γ</semantics>-Al2O3 carrier material was prepared using the precipitation method and a new hydrogen sensor was prepared by doping and modifying it with graphene. During the detecting part of the experiment, the voltage–current–temperature detecting system was designed based on the principle of voltage division and shunt, and the theoretical operating temperature computational model was established in parallel. After testing, it was shown that the sensor had a good linear relationship for the range of 1000–10,000 ppm H2; the operating temperature was only 176 °C at 1.4 V operating voltage, the T90 response time was 6.69 s, and the average sensitivity and temperature rise characteristics were 28.23 mV/1% H2 and 36.77 °C/1% H2, respectively. Moreover, the calculated theoretical operating temperature and the measured temperature were basically consistent. This work provides a useful reference for further exploration of H2 sensors.